2019
DOI: 10.1080/20464177.2019.1684165
|View full text |Cite
|
Sign up to set email alerts
|

Underwater thrust vectoring based on inflated surface

Abstract: The traditional way to underwater thrust vectoring is mainly based on a specially designed mechanical system which provides the propulsion system additional degree of freedom. This method is effective in field applications. However, there are several drawbacks such as complex structure and large dead weight. In this paper, a new type of thrust vectoring method, based on inflated surface is proposed. There are six inflatable surfaces uniformly distributed around the axis of the propulsor. The mechanism of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Concerning to flying humanoids, snake aerial manipulators can be seen as the subsystems or limbs of this kind of robots [45]- [47]. Finally, with respect to non-flying vehicles it must be indicated that extrapolations of the topics described in this text to vehicles different from aircraft can be found at [48]- [52]. More details about the aforementioned drawbacks and other important problems will be analysed in the next sections.…”
Section: Applications and Drawbacksmentioning
confidence: 99%
“…Concerning to flying humanoids, snake aerial manipulators can be seen as the subsystems or limbs of this kind of robots [45]- [47]. Finally, with respect to non-flying vehicles it must be indicated that extrapolations of the topics described in this text to vehicles different from aircraft can be found at [48]- [52]. More details about the aforementioned drawbacks and other important problems will be analysed in the next sections.…”
Section: Applications and Drawbacksmentioning
confidence: 99%